Analysis and Epidemiology of Viral Hepatitis Illnesses in Khorazm Region - Alimovich, Masharipov Otaboy; Ataboevich, Masharipov Ogabek (PT. Antis International Publisher, 2024)
According to the World Health Organization, liver cirrhosis is the tenth leading cause of death among all diseases. Despite the development of a number of recommendations worldwide in recent years, there is a sharp difference between the drugs used in the pharmacotherapy of liver diseases and the drugs indicated in the treatment standards. This, in turn, requires deep pharmacoepidemiological research [1]. Treatment of patients with chronic liver diseases requires significant financial costs. These are not only the costs of treatment, but also indirect costs, which are associated with temporary loss of working capacity[2]. Epidemiological control of anthroponoses is multifaceted, a dynamic study of the disease, not only operative control of the disease, but also a deep investigation of the ecology, biology and distribution area of the causative agent. Viral hepatitis is one of the most common viral infectious diseases in the world. According to the information provided by the World Health Organization, 2 billion people are infected with viral hepatitis on earth, which corresponds to 1 out of every 3 people on earth [3]. Every year, parenteral viral hepatitis kills more than 1 million people worldwide, which is equal to the number of deaths from tuberculosis and more than the number of deaths from HIV. In 2021, despite the widespread use of a highly effective vaccine against viral hepatitis V, 1.5 million people were infected with hepatitis V [4]. The medical and social conditions of Uzbekistan include the hyperendemic region due to the specificity of the number of family members, different levels of virus infection in the region due to the age structure, and the spread of infection due to the ethnic identity of the local population [5,6]. In screening studies conducted by a number of authors, it was found that 5.6% of healthy population tested in our country have anti-HCV and 8.3% have HBsAg.